Very low monomethyl fumarate exposure via human milk: a case report—a contribution from the ConcePTION project - Van Neste, Martje; Nauwelaerts, Nina; Ceulemans, Michael; Cuppers, Benedikte; Annaert, Pieter; Smits, Anne; Allegaert, Karel (Frontiers in Public Health, 2024)
Introduction While breastfeeding is recommended, knowledge regarding medicine transfer to human milk and its safety for nursing infants is limited. Only one paper has previously described dimethyl fumarate (DMF) transfer during breastfeeding in two patients at 5 and 6 months postpartum, respectively. The current case report describes maternal pharmacokinetic data of monomethyl fumarate (MMF), the active metabolite of DMF, and infant exposure estimations of MMF at 3 months postpartum. Methods A 32-year-old Caucasian woman started DMF therapy (120 mg, 2x/day) for multiple sclerosis at 3 months postpartum, after weaning her infant from breastfeeding. On day 99 after birth, the patient collected four milk samples over 24 h after 6 days of treatment at the initial dose. Additionally, a single maternal blood sample was collected to calculate the milk-to-plasma (M/P) ratio. The samples were analyzed using liquid chromatography coupled with the mass spectrometry method. Results A wide range of measured steady-state concentrations of MMF (5.5-83.5 ng/mL) was observed in human milk samples. Estimated daily infant dosage values for MMF, calculated with 150 and 200 mL/kg/day human milk intake, were 5.76 and 7.68 μg/kg/day, and the relative infant doses were 0.16 and 0.22%. The observed mean M/P ratio was 0.059, similar to the M/P ratio predicted using the empirical Koshimichi model (0.06). Discussion Combining this case report with the two previously described cases, the estimated infant exposure is low, albeit with relevant intra- and inter-patient variabilities. Research should further focus on infant exposure and safety.